Teoretical basis for the study of reparation by the state physical person, the victim of a criminal offence - Наталія Анатоліївна Хмельова (Проблеми Законності, 2016)
Theoretical aspects of harm caused a criminal offence, that is, damage that is the basis for the adoption of measures to ensure reparation to the victim, in the science of civil procedural law received significant attention. However, despite the serious scientific elaboration of this problem and its issues, still have a lot of issues that are still insufficiently study, while they are essential for the theory of civil law. Analysis of recent research gives reason to believe that the affected problems has been the subject of research by scholars such as G. A. Atanesyan, S. P. Golubyatnikov, B. T. Bezlepkin, M. I. Goshovsky, O. I. Kuchinska, V. T. Nor, and others. However, the update of the regulatory material, in particular amendments to the Civil code of Ukraine, adoption of the new Criminal procedural code of Ukraine, can not affect scientific and practical interest in the conditions of modernity.